1995
DOI: 10.1212/wnl.45.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Visual field loss in senile dementia of the Alzheimer's type

Abstract: Although automated perimetry requires considerable patient cooperation, many patients with SDAT can produce reliable visual field results. These patients exhibit significant reductions in global sensitivity. Visual field loss in SDAT is most pronounced in the inferonasal and inferotemporal arcuate regions of the visual field but also involves the central field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 12 publications
11
81
0
5
Order By: Relevance
“…This is consistent with previous OCT findings 13, 15, 16, 17, 18, 20. The preferential loss of fibers in the superior quadrant is also compatible with the predominant inferior visual field defect documented in AD patients 56. It is intriguing that the superior sector contains the largest fibers of the optic nerve and previous postmortem studies documented a preferential loss of the larger axons, suggesting early involvement of the magnocellular RGCs in AD 11.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous OCT findings 13, 15, 16, 17, 18, 20. The preferential loss of fibers in the superior quadrant is also compatible with the predominant inferior visual field defect documented in AD patients 56. It is intriguing that the superior sector contains the largest fibers of the optic nerve and previous postmortem studies documented a preferential loss of the larger axons, suggesting early involvement of the magnocellular RGCs in AD 11.…”
Section: Discussionsupporting
confidence: 91%
“…This region corresponds with the inferior visual field and these changes could explain the vision loss reported in this area in AD [48]. Other OCT studies have reported different patterns of RNFL loss (general, parapapillary and macular) [119,[135][136].…”
Section: (Figure 4)mentioning
confidence: 69%
“…Visual disturbance is often an early complaint of AD patients [46][47] and studies have reported reduced visual performance on tests of visual field [48][49], color vision [50][51][52], contrast sensitivity [53][54][55], backward masking [56][57], visual attention, motion perception, shape-from motion, visuo-spatial construction, visual memory [58][59][60], delayed saccadic initiation and movement and fixation problems [47,[61][62][63]. However, none of these deficiencies are specific to AD.…”
Section: Vision In Alzheimer's Diseasementioning
confidence: 99%
“…Alzheimer's disease may present with visual field loss 13 and more commonly field defects are recognised during the course of the disease. 14,15 However, presentation with reduced visual acuity is unusual.…”
Section: Discussionmentioning
confidence: 99%